Body balance and isokinetic strength assessment of the flexors and knee extensors in a sarcopenic, diabetic elderly individual with complete visual impairment: a comparative case study - Müller, Daniela Virote Kassick; Tavares, Graziela Morgana Silva; Gottlieb, Maria Gabriela Valle; Schneider, Rodolfo Herberto (Journal of Health Care, 2016)
Objective: assess, describe and compare the body balance and the muscle strength of knee flexors andextensors of a sarcopenic elderly individual with type 2 Diabletes Mellitus (DM2) and total visualimpairment, with two other elderlies in similar conditions, but without visual impairment. Casedescription: This descriptive-comparative study assessed a sarcopenic elderly patient with DM2 and totalvisual impairment (1 subject), comparing him with 2 sarcopenics elderly patients with DM2, but withoutvisual impairment (subjects 2 and 3). Balance variables were evaluated by the Sensory Organization Test(SOT), using NeuroComÂ® International Smart Equitestâ„¢ in six different conditions in which posturalcontrol mechanisms were requested in different ways. For each condition three attempts were performed,generating then a performance average for each condition. It was later gathered data on knee flexorsand extensors muscle strength and power by Biodex System 4 ProÂ® isokinetic dynamometer at speeds of60 and 180º/ sec. Conclusion: The study results showed that the subject 1 even presenting total visualimpairment presented a good body balance when compared with the overall average, and with subjects 2and 3, but presented a greater muscle strength deficit in comparison with subjects 2 and 3.
Keywords: elderly; postural balance; visual impairment; sarcopenia